Geomagnetism as an independent science - Muniz Barreto, Luiz (1997)
At its beginning, Geomagnetism was involved into a mystical atmosphere. Neckham and Norman's experiments, and the practical use of the compass by Columbus had no significance to disconnect it from a mysterious understanding. In spite of the magnificent Gilbert's treatise, the general belief about Geomagnetism remained enigmatic. Gauss'creative methods to measure the Earth's Magnetism were the most important step to place geomagnetic phenomena into the frame of physical rational sciences. Many of those phenomena continued to be considered as low atmospheric events, and they were treated as meteorological ones. In 1851, Liáis proved that a typical geomagnetic phenomena, the aurora borealis, occurs far from the "meteorological atmosphere", but his results were only recognized in our century, when IATME, and latter, IAGA were created. The influence of Geomagnetism as a seed of great scientific programs (e. g. the 1st. and the 2nd. Polar Years, and the IGY) puts Geomagnetism in its proper place as an independent science.